Penyakit mosaik pisang, reaksi inang dan pemurnian virus: ( Banana mosaic disease, host reaction and virus purification) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT Banana var. Koja showed mosaic symptoms obtained in Kotagede, Yogyakarta used in the studies. The virus was then isolated with single lesion method on Chenopodium aniaranticolor, and propagated on Nicotiana tabacum var. Xanthi. The results of host reaction studyshowed that infected Nicotiana tabacum var Xanthi, N. tabacum var. Samsun and Cucumis sativus and Lycopersicon esculent= produced systemic symptoms, while Chenopodium amarandcolor produced necrotic local lesions. InfectedNipa unguiculat